2020
DOI: 10.1007/s11010-020-03974-6
|View full text |Cite
|
Sign up to set email alerts
|

Histamine augments collagen content via H1 receptor stimulation in cultures of myofibroblasts taken from wound granulation tissue

Abstract: The inflammatory reaction influences the deposition of collagen within wound granulation tissue. The aim of the present study is to determine whether histamine acting directly on myofibroblasts derived from wound granulation tissue may influence collagen deposition. It also identifies the histamine receptor involved in this process. The experiments were carried out on cells isolated from the granulation tissue of a wound model (a polypropylene net inserted subcutaneously to rats) or intact rat skin. Collagen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Hence, it appears that different histamine receptors may be involved in the regulation of collagen content, although the obtained results are dependent on the experimental model, and the selected tissue or species. Previous studies have suggested that different types of histamine receptors participate in the regulation of collagen deposition in various organs or tissues (19,(32)(33)(34). This phenomenon could be dependent on the varying influence of the extracellular environment on myofibroblasts (2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, it appears that different histamine receptors may be involved in the regulation of collagen content, although the obtained results are dependent on the experimental model, and the selected tissue or species. Previous studies have suggested that different types of histamine receptors participate in the regulation of collagen deposition in various organs or tissues (19,(32)(33)(34). This phenomenon could be dependent on the varying influence of the extracellular environment on myofibroblasts (2).…”
Section: Discussionmentioning
confidence: 97%
“…Previously, it has been proposed that in the cardiac myofibroblasts obtained from a myocardial infarction scar, the histamine content is mediated by the H 3 receptor (19). However, the effect of histamine was found to be influenced by the H 1 receptor in myofibroblasts from wound granulation tissue (18,32). H 1 receptor activation appears to be involved in the regulation of collagen metabolism within dermal fibroblasts ( 27), whereas blockade of the H 2 receptor decreased collagen type I gene expression in human fibroblasts (28).…”
Section: Discussionmentioning
confidence: 99%
“…In rabbit ear hyperplastic scar, long-acting intra-lesioned injection of histamine drug can inhibit the TGF beta l/Smad3 signalling pathway to reduce the collagen synthesis and I/collagen type III proportion, thereby inhibiting scar hyperplasia (41). The regulatory effect of histamine on wound broblast function (activity/metabolic activity or TGFβ1 secretion) is determined by H1 receptor stimulation (42,43). CPM acts as an H1 receptor antagonist with a more substantial antihistamine effect than diphenhydramine and others, and it has been applied clinically as an antihistamine with less dosage and side effects (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine, another substance secreted by MCs, also induces fibrosis. It is reported that histamine stimulates fibroblast proliferation and collagen synthesis [ 91 , 92 ]. Histamine has four receptors: H1R, H2R, H3R and H4R.…”
Section: Pro-allergic and Inflammatory Actions Of Mcsmentioning
confidence: 99%